Competency assessment of short free text answers - Lajis, Adidah; Abdul Aziz, Normaziah (2014)
The increased adoption of competency-based education has posed the need of an automated competency assessment. Most of the existing assisted assessment does not cater for competency assessment. The high percentage on the use of short free text answer as competency assessment shows that the need of the competency assisted assessment is urgent. This paper studies on the need and also review on existing assisted assessments focusing on short free text answer. A Node Link (NL) Scoring technique is proposed as an alternative automated solution to assess learners’ competency in short free text answers. Keyword: competency assessment; short free text answers; Node Link Scoring technique